Household Catastrophic Health Expenditure - A Daneshkohan; M Karami; F Najafi; B Karami Matin (Tehran University of Medical Sciences, 2011)
Background: Fairness in financial contribution for health was determined by WHO (World Health Report, 2000) as the third goal of health systems which is measured by fairness in financial contribution index (FFCI). The aim of this study was to estimate FFCI and quantify extent of catastrophic household heath expenditures."nMethods: We conducted a descriptive study during May 2008. Subjects were chosen by "Systematic Random sampling" among residents of Maskan's population- based research center (Maskan Center) in Kermanshah, Iran. After completing informed consent form, we collected data using a questionnaire by interview with head of family. In order to describing data and estimating FFCI, we used descriptive statistics and WHO methodology, respectively. Households with catastrophic expenditures and impoverished households were defined as those with health expenditures over 40% and 50% of their ability to pay, respectively."nResults: The mean age of head of families was 48.96±12.86 years. From 189; 12.7% of household's heads were female. 75.1% of households were covered by at least one health insurance scheme. FFCI was 0.57. The proportion of households facing catastrophic health expenditures was 22.2% (95% CI=16.3%-28.1%)."nConclusion: The rate of FFCI among participants implied an inequality in health financing contribution. In addition, many of households (22.2%) faced catastrophic health expenditures while according to WHO estimation, the figure in the whole country was 2% in 1999. Our study revealed the importance of protecting households against the costs of ill-health.